MONOGRAPHIC SECTION 2, Foreword: Do "Perspective", "Point of View", "Frame" and "Scenario" refer to the same concept? MONOGRAPHIC SECTION 2, Foreword: Do "Perspective", "Point of View", "Frame" and "Scenario" refer to the same concept? - Brugnami, Enrico (Analysis. Journal of Philosophical Research, 2024)
Foreword to the second monographic section: Do "Perspective", "Point of View", "Frame" and "Scenario" refer to the same concept?